Mechanical Properties of Corroded-Damaged Reinforced Concrete Pile-supporting Wharves - Cecielle N. Dacuan; Virgilio Abellana; Hana Astrid Canseco (Civil Engineering Journal, 2020)
Corrosion is one of the significant deteriorations of reinforced concrete structures. It accelerated the performance loss of the structures, leading to a cross-sectional reduction of steel, which affects its mechanical properties, particularly its tensile capacity and ductility. The purpose of this study is to assess the serviceability and safety of corroded-damaged structures, particularly those exposed to aggressive marine environments. A total of 54 pcs of 150 mm-diameter and 300mm-height of cylindrical specimen were cast. Small-scaled specimens were accelerated to corrosion using impressed current techniques with a constant current density of 200 µA/cm2. Samples were immersed in a simulated environment with a 5% solution of sodium bicarbonate during corrosion acceleration. Corrosion alters the surface configuration of the steel bar. Pitting corrosions due to chloride aggression causes the residual cross-sectional area of corroded rebars to no longer round and varies considerably along its circumference and length. The reduction of the steel cross-sectional area has a significant impact on the degradation of the strength and durability of reinforcing structures. The residual capacity of the corroded reinforcement decreases with the reduction of the cross-sectional area of the steel reinforcement. The rate of corrosion affects the extent of the remaining service life of a corroded reinforced concrete structure. Doi: 10.28991/cej-2020-03091624 Full Text: PDF